Etika Islami Dan Kecurangan Pada Profesi Akuntan Manajemen: Dampak Moderasi Kualitas Pengendalian Internal Dan Lingkungan Kerja - Sugiyarti Fatma Laela; Rahil S Akun (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
This study aims to analyze the influence of Islamic ethics on fraudulent behavior. In addition, this study also analyzes the moderating impact of the internal control system and work environment variables on the relationship between ethics and fraud. All variables were measured using a questionnaire instrument. By using respondents of 131 management accountant from various industries, the research uses SEM-PLS to test the proposed hypotheses. The results of the study are able to answer the three objectives, namely (1) Islamic ethics reduce fraudulent behavior of management accountants, (2) an effective internal control system strengthens the influence of Islamic ethics in reducing fraudulent behavior, (3) a conducive work environment strengthens the influence of ethics in reduce fraudulent behavior. This study complements the empirical studies of Islamic ethics for the accounting profession. The research implication for the management accounting profession is the need to consider the universal aspect of religiosity as part of the professional code of ethics. For management, this study supports the need for the design and implementation of a healthy and effective internal control system and organizational environment.